PROFIL PASIEN GASTROESOPHAGEAL REFLUX DISEASE DI RUMAH SAKIT ISLAM SITI RAHMAH PADANG TAHUN 2017-2018 - Gangga Mahatma; Yusti Siana; Abdul Raziq Jamil; Ade Riadi; Fira Amalia (Yayasan Nusantara Hasana Berdikari, 2023)
Gastroesophageal reflux disease (GERD) is defined as a symptom or mucosal damage produced by abnormal reflux of gastric contents into the esophagus or beyond, into the oral cavity (including the larynx) or the lungs. Risk factors for GERD include: age, gender, smoking history and others. Symptoms of GERD are divided into 3 groups, typical symptoms, atypical symptoms and extraesophageal symptoms. Knowing the profile of GERD patients at the Siti Rahmah Islamic Hospital in Padang for the 2017-2018 period. This study uses descriptive research using secondary data derived from the patient's medical record. Performed at the medical record section of RSI Siti Rahmah Padang. When the research was conducted from January - March 2021, the population reached was 96 with a total random sampling technique. The highest age is over 50 years, namely 67 people (69,8%). Male, namely 61 people (63.5%). Typical symptoms were 68 people (70.8%). History of smoking is 54 people (56.2%). The highest GERD patients is over 50 years old with male sex, the most symptoms are typical symptoms and a history of smokings.